Perancangan Proyek Botanical Garden di Denpasar Dengan Pendalaman Sense of Place Oleh Konsultan Arsitektur Locus.Artifex - Sharfan, Muhammad Alfaza; Anggraini, Lya Dewi (KREASI, 2024)
Numerous human and natural resources, as well as a rich cultural heritage, exist in Indonesia. But many of us forget our identity, so we don’t realize that we are slowly forgetting our culture. Therefore, Locus. Artifex wants to raise the locality issue through architectural design to revive Indonesian culture and wealth. Planning a botanical garden in Denpasar with an in-depth sense of place, aims to create a green space that not only functions as a place for flora conservation but also as a centre for education, recreation, and the preservation of local culture. The design concept in this design combines traditional Balinese style with contemporary style by highlighting local conventional elements as the building’s characteristic. The design of the Denpasar Botanical Garden is inspired by the shape and layout of traditional Balinese house architecture by applying zoning from the Tri-Mandala, Sanga mandala, Natah, tropical building forms, and Bale. The zoning concept applied is the tri-mandala concept, broadly divided into 3 areas: utama, madya, and nista. The design method used in this design is to use design icons. This approach is used to highlight a traditional theme in a modern way, utilizing literature and traditional forms as the foundation for a design that combines contemporary forms to create something truly unique.